Meteorological conditions in a thinner Arctic sea ice regime from winter to summer during the Norwegian Young Sea Ice expedition (N‐ICE2015). Issue 14 (17th July 2017) - Cohen, Lana; Hudson, Stephen R.; Walden, Von P.; Graham, Robert M.; Granskog, Mats A.
Abstract: Atmospheric measurements were made over Arctic sea ice north of Svalbard from winter to early summer (January–June) 2015 during the Norwegian Young Sea Ice (N‐ICE2015) expedition. These measurements, which are available publicly, represent a comprehensive meteorological data set covering the seasonal transition in the Arctic Basin over the new, thinner sea ice regime. Winter was characterized by a succession of storms that produced short‐lived (less than 48 h) temperature increases of 20 to 30 K at the surface. These storms were driven by the hemispheric scale circulation pattern with a large meridional component of the polar jet stream steering North Atlantic storms into the high Arctic. Nonstorm periods during winter were characterized by strong surface temperature inversions due to strong radiative cooling ("radiatively clear state"). The strength and depth of these inversions were similar to those during the Surface Heat Budget of the Arctic Ocean (SHEBA) campaign. In contrast, atmospheric profiles during the "opaquely cloudy state" were different to those from SHEBA due to differences in the synoptic conditions and location within the ice pack. Storm events observed during spring/summer were the result of synoptic systems located in the Barents Sea and the Arctic Basin rather than passing directly over N‐ICE2015. These synoptic systems were driven by a large‐scale circulation pattern typical of recent years, with an Arctic Dipole pattern developing during June. Surface temperatures became near‐constant 0°C on 1 June marking the beginning of summer. Atmospheric profiles during the spring and early summer show persistent lifted temperature and moisture inversions that are indicative of clouds and cloud processes. Key Points: Analysis of a new comprehensive meteorological data set over Arctic sea ice from winter to summer Measurements of Arctic storms during winter show large but short‐lived impact on atmospheric temperature Spring/summer atmosphere is characterized by persistent temperature and humidity inversions indicative of clouds